We are given the expression
![x^(2)+6x\text{ -27}](https://img.qammunity.org/2023/formulas/mathematics/college/usaygai019si1avvwvi7zr44yvwcjshudi.png)
and told to factor it. First, recall that this expression looks similar to this one
![x^(2)+bx+c](https://img.qammunity.org/2023/formulas/mathematics/college/e38eovwadyo56ix1rh0641vxro3smfqvvp.png)
where in our case b=6 and c=-27. To check if this expression can be factored by using integers, we should look for two integers, say e and f such that the product of e and f is equal to c and the sum of e and f is equal to b. That is
![e\cdot f\text{ = -27}](https://img.qammunity.org/2023/formulas/mathematics/college/6492dqfunakgil7v2im3o0bd4d60tmxa2s.png)
and
![e+f=6](https://img.qammunity.org/2023/formulas/mathematics/college/b5wci6truo6byyw0bo9cyf06y57wb1u9h3.png)
At first, notice that c=-27 is a negative number. Since -27 is the product of two integers, for it to be a negative number it must happen that at least one of them is a positive number and the other one is a negative number. Suppose that e>0 and that f<0. Now, we take a look at the factors of 27. Note that
![27=1\cdot3\cdot3\cdot3](https://img.qammunity.org/2023/formulas/mathematics/college/5u7a29i7zcy5wy4vkp157hqv4dez4gkg1z.png)
Now, in the factors of 27, we should look for a way to group them such that we get the numbers e and f we are looking for. For example, le us group it as follows
![(1)\cdot(3\cdot3\cdot3)=(1)\cdot(27)](https://img.qammunity.org/2023/formulas/mathematics/college/5279x8vdipki8bwvz0di1jib50snrkkk6l.png)
We see that 27=27*1. So for example let us take e=27 and f = -1 (remember that they should have different signs). This fulfills the criteria that e*f = -27. However e+f = 26, which is not 6. So this agrupation doesn't work.
Now let us try this
![(1\cdot3)\cdot(3\cdot3)\text{ = 3}\cdot9](https://img.qammunity.org/2023/formulas/mathematics/college/z2b3eonyt29bncexd5605eyrdej94d3j8n.png)
In this case we get the numbers 9 and 3. Let us take e=9 and f=-3. This fulfills that e*f=-27. Also we have that e+f = 9-3=6 which is what we wanted. So, our numbers are
![e=9,\text{ f=-3}](https://img.qammunity.org/2023/formulas/mathematics/college/n0twvx3z5uhoxmnycc0wz0ohq147ssiuue.png)
Now, to find each factor we write each factor as follows